Metrosexual Masculinities - Hall, M. author. aut Link
XI, 196 p.
Keywords: Modern men the world over are becoming increasingly fascinated with their image, spending more of their disposable income on beautification products and services. This book examines 'metrosexuality', highlighting the negotiation and construction of masculinities and sexualities in the twenty-first century.